The Role of The Marketing Mix Factors in Hospital Selection - Rahmawati, Yuni; Susilowati, Susilowati (Rumah Sakit Akademik Universitas Gadjah Mada, 2023)
Background: The problems faced by Soerojo Hospital is currently decreasing the number of outpatient visits and decreasing customer satisfaction. Marketing mix analysis based on satisfaction surveys which on average are good based on hospital customer perceptions and targeted revenue targets from out-of-pocket sources of 30 percent require the right marketing mix tactics for potential customers in the comunity. This study will help Soerojo Hospital choose dominant factor of the marketing mix in hospital selection for making optimal marketing strategy. The aims of this study was to identify the role of the marketing mix factors on people's decisions in hospital selection. Materials and Methods: This study was conducted with a descriptive, quantitative approach, cross sectional research design, 385 respondents were surveyed with questionnaires and data analysis was carried out with program packages. Results: The components of the marketing mix that occupy the top three positions are the location component with a median of 4.67(1-5), the process component with a median of 4.60 (1-5) and the cost component with a median of 4.50 (1-5). There was a significant difference between the groups who choose and did not choose Soerojo mental hospital in the doctor/staff and promotion (p value <0.05). Conclusion: The location, process and cost components are the components of the marketing mix that most influence the decision to choose a hospital. Suggestions for improvements that can be made by RSJ Prof. Dr. Soerojo Magelang based on the results of this study.